PENGAJARAN SAINS MELALUI DEMONSTRASI: PENDEKATAN INOVATIF UNTUK MENINGKATKAN LITERASI SAINS LINGKUNGAN SISWA - Erma Suryani Sahabuddin; Liskawati Liskawati; Syamsiah Syamsiah (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The issue in this study is the poor scientific learning results in class V at UPT Public Elementary School, 127 Inpres Komara I, Polut District, Takalar Regency. This study's aim was to describe how the demonstrative learning model was used to enhance fifth-grade students' scientific learning results at UPT Public Elementary School 127 Inpres Komara I in Takalar Regency's Polut District. This research strategy is qualitative. This kind of study is called classroom action research, and it entails planning, carrying it out, monitoring it, and reflecting on it. The demonstration learning paradigm and science learning outcomes are the main topics of this study. Teachers and fifth-grade children at UPT Public Elementary School, 127 Inpres Komara I, Polut District, Takalar Regency, served as the study's subjects. 7 boys and 6 girls who participated in the even semester of the 2022–2023 academic year: observation data collection methods, assessments, and paperwork. The three data analysis approaches used in this study are data reduction, data presentation, and conclusion. The analysis of the research's findings reveals a significant growth in each cycle. Cycle I test scores with sufficient qualifications increased in cycle II with appropriate qualifications. The data analysis results showed that demonstration learning might enhance student learning outcomes in science in class V UPT Public Elementary School 127 Inpres Komara I, Polut District, Takalar Regency.